Macrostructural Analysis of the Dynamics of the Two-Sector Economy - O. S. Sukharev; E. N. Voronchikhina (Финансы: теория и практика, 2024)
The article is devoted to an empirical demonstration of the application of macrostructural analysis of the dynamics of the Russian economy, represented by the capital goods and consumer goods sectors, including the intangible sphere.   The purpose of the study is the formation of an algorithm for macrostructural analysis of the two-sector Russian economy with the identification of the main patterns and relationships of their joint dynamics — contribution to the overall growth rate, price dynamics, and the definition of a model for further development.   The methodology consists of the theory of economic growth, structural analysis, empirical and regression methods for studying the relationships of relevant parameters. The main result of the study is the formation of an algorithm for macrostructural analysis and its application to the Russian economy at the specified time interval with the highlighting of the main characteristics of the structural dynamics represented by the capital goods and consumer goods sectors. The relationship between these sectors, mutual determination determines not only the current model of development in Russia, but provide opportunities for future economic growth, since the creation of investment and consumer products form the foundation of a growing economy. The study found that the predominance of the consumer goods sector in the Russian GDP structure not only determined the current dynamics, but also the potential for the growth rate of the capital goods sector, as well as the level of its efficiency, which affects the dynamics of prices in the sector. The growth rates of the sectors influenced each other, but the resulting structural change, in the form of a decrease in the share of the capital goods sector, was accompanied by both a reduction and an increase in overall inflation. And any impulse of acceleration of capital goods led to greater rise in sectoral prices than equivalent accelerations in the consumer goods sector. Thus, the proposed algorithm of macrostructural analysis allowed us to reveal the specifics of the structural dynamics of the Russian economy, revealing the determinants of non-monetary inflation. The perspective of the study is to assess the contribution of sectoral dynamics to a higher price level and the selection of policy instruments that affect the structure, ensuring both its growth and qualitative transformation in accordance with development goals.